Multi-stage typhoon-induced wind effects on offshore wind turbines using a data-driven wind speed field model. (April 2022) - Wang, H.; Ke, S.T.; Wang, T.G.; Kareem, A.; Hu, L.; Ge, Y.J.
Abstract: In light of spatiotemporal variations in a typhoon wind speed field, this paper proposes a multi-stage analysis framework for typhoon-induced wind effects on offshore wind turbines. In this framework, the influence of different typhoon impact stages on the mean wind speed profile, typhoon intensities, and spectral characteristics are considered utilizing an enhanced wind speed field model. To this end, an enhanced mean wind speed profile model under marine typhoon conditions is first derived based on dropsonde measurements. This profile model modifies conventional power/logarithmic laws so as to capture accurately the effects of typhoon-induced low-level jets within the height range of 0–500 m above the sea surface. It accounts for the parameters representing typhoon characteristics such as RMW (radius of maximum winds) and boundary layer wind speed. The turbulence intensity profile is also enriched by combining the empirical turbulence ratio with the data-driven updated mean wind profile. A generalized six parameter typhoon wind spectrum is also introduced using wind field measurements during typhoon "Hagupit". The resulting wind speed field model is calibrated concerning four impact stages of typhoon "Hagupit", demonstrating its ability to characterize multi-stage features. Compared to existing models prescribed in codes/specifications, the enhanced multi-stage model closely matches measurements while being slightly on the conservative side. The framework proposed including the enhanced model is then utilized to analyze typhoon-induced wind effects on a 205 m offshore wind turbine. Results reflect the apparent influence of multiple impact stages of a typhoon. Moreover, the enhanced wind profile models may lead to a higher level of response at critical sections of both the turbine blades and tower than the model prescribed in the current standard.